Workshop proceedings of imp-act thematic group meeting on understanding the wider impacts of microfinance - Halder, Shantana R. (BRAC, 2019)
The proceedings brief the outcomes of the third Imp-Act thematic group meeting on understanding the wider impacts of micro finance (MF) as a part of the three-year Global Impact Assessment Project funded by Ford Foundation. The main objective of this thematic group meeting was deepening the understanding of issues around the direct and indirect impacts of MF services on clients and non-clients, their communities and the local and national economies. The proceeding summarizes findings of all the 17 papers presented by different authors coming from all over the world during the first two day sessions. The authors mainly shared experiences of different MF institutions working in Latin American, South Asian, African and Sub-Saharan countries and their impacts on the changes in socio-political and economic lives at micro, meso- and as well as macro levels. It is also documented all the issues raised during discussions, which have taken place after each and every presentation. There is a consensus in understanding that although it is now well established about the positive contribution of the sector in the development chain, for better understanding of MF impact at different levels there is a need for detailing out further certain issues on, for example, i. Group formation: Need for distinguishing between good/bad approaches; ii. Research should have appeal across disciplines for maximizing impact; iii. Need to think about strategy & methods; iv. Strategy & tactic's (research areas, international approach, dissemination); v. Studies on strategic partnership to provide credit plus plus; vi. Trend and implications of commercialization in MF; vii. Gender needs to be a core underlying theme in all analysis; viii. Financial services (product innovation, spreading and deepening coverage) ix. Need to focus on markets and multi market outcomes; x. Networking to maximize value added and xi. Gender as an agenda and also as a theme.